The "Great Resignation" in perspective. (Monthly Labor Review, 2022)
The article offers perspectives on trends in job quitting rates or a phenomenon called the Great Resignation in the U.S. Topics include the variation in quit rates measured using a sample rather than a census of establishments, an analysis of data on quit rates predating the U.S. Bureau of Labor Statistics (BLS) Job Openings and Labor Turnover Survey (JOLTS) program to determine whether it is relative to those in the 20th-century, and the impact of the Covid-19 pandemic recession on quit rates.